2019
DOI: 10.1080/13621718.2019.1680483
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing nugget size and weldable current range of ultra-high-strength steel using multi-pulse resistance spot welding

Abstract: This paper presents an innovative approach that uses a pulse-profile to improve the welding quality of CP1180 steel in resistance spot welding process. Three pulses with two cooling times were used in the developed multi-pulse welding (MPW) schedule. The experimental results show that the first pulse increases the contact area between the sheets to improve the current flow pattern. The second pulse was designed to extend the sheet-to-sheet contact area and corona bond for preventing rapid nugget growth. Using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The FZ size depends upon the amount of heat generated during RSW. The physical principal for achieving the heat generation in the RSW process is defined by Joule’s heating equation given below [ 32 ]. where is the heat generated (J), is the current applied (A), is the total resistance (Ω) and is the time for which current is applied (s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The FZ size depends upon the amount of heat generated during RSW. The physical principal for achieving the heat generation in the RSW process is defined by Joule’s heating equation given below [ 32 ]. where is the heat generated (J), is the current applied (A), is the total resistance (Ω) and is the time for which current is applied (s).…”
Section: Resultsmentioning
confidence: 99%
“…The FZ size depends upon the amount of heat generated during RSW. The physical principal for achieving the heat generation in the RSW process is defined by Joule's heating equation given below [32].…”
Section: Enlargement Of Fzmentioning
confidence: 99%
“…In the automobile industry, resistance spot welding (RSW) is a fusion welding process that is used to assemble steel sheets; in this process, the heat required for melting is produced by passing high current through copper electrodes [4][5][6]. However, Zn coating is prone to liquid metal embrittlement (LME) cracking during RSW [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…RSW welding process can be easily automated [14,15], robotized, therefore RSW is also an optimal process for mass production. RSW is also one of the most used welding process in car body manufacturing.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extensive research hase been done in the field of the application of different pulsed welding technologies in the case of HSS welding. Kim et al [15] investigated different pulse profiles to improve the weld quality of CP1180 steel. They have found that the volume of the weld nugget can be increased by pulse welding, and the weldable current range can be extended compared to single pulse welding.…”
Section: Introductionmentioning
confidence: 99%